Study Of Socioeconomic Factors in Relation to Depression Among Elderly People Living in Rural Area Of Andhra Pradesh - Sharvanan Eshwaran Udayar; Santosh D Patil; Kandha Vadivel (Medsci Publications, 2016)
Background: The world population has been experiencing significant ageing. With the increase in life expectancy, rapidly changing social and physical environment, breaking of traditional protective measures, increase in morbidity due to chronic non communicable disease will lead to increased psychological disorders like depression. This study was conducted to find out the prevalence of depression district and its relation to socio demographic factors of the elderly population.. Materials and methods: A Cross sectional community based study was undertaken for a period of six months (Jan-June 2014) in the villages of V. Kota and Shanthipuram mandals of Chittoor district in Andhra Pradesh state. Data was collected regarding socio-demographic profile, availing of old age pension, depression using GDS score & analyzed using SPSS software. Results: 418 elderly people were included in the study. The overall prevelance of depression was around 44.1%.Statistically significant association found between depression and socio demographic factors like aged more than 80 year, those who are separated/widowed and belonging to low socio economic status. Conclusions: higher prevalence of depression during later years of life, those who are separated, loss of spouse and belonging to lower socio economic status and these findings were statistically significant.